Analisis Kinerja Reksa Dana Saham Dengan Menggunakan Metode Sharpe Dan Jensen Untuk Periode 2005 – 2009 - Pujiarti, Trisiwi; Dewi, Farida Ratna (IPB University, 2011)
Every investment option are risky because of uncertainty. Each investment instruments have different risk levels. Measurement of risk impact depends on the type of Investment.